Hubungan Tingkat Kesiapsiagaan Masyarakat Menghadapi Bencana Gempa Bumi dan Tsunami Dengan Tingkat Kecemasan Masyarakat Di Dusun Leko RT/RW 035/007 Kelurahan Wolomarang - Yuliani Pitang; Maria Lambertina Barek Aran; Adelheid Riswanti Herminsih (Jurnal Ilmiah Wahana Pendidikan, 2023)
Earthquake and tsunami disasters are one of the factors that cause people to feel anxious. Disaster preparedness is one of the disaster management efforts that can reduce the risk of loss and loss of life caused by disasters. This study aims to explain the relationship between the level of community preparedness for earthquake and tsunami disasters and the level of community anxiety in Dusun Leko This research is a correlative analytic study with a cross sectional approach. The population in this study were 145 people from Wurring Leko with a sample size of 42 respondents who were taken using a purposive sampling technique. The instrument in the study used the STAI questionnaire for independent variables and the dependent variable used a questionnaire from LIPI UNESCO/ISDR 2006 and then tested it using the Spearman rank test.The results showed that 17 respondents (40.5%) were in the unprepared category and 33 respondents (78.6%) were in the moderate anxiety category. Spearman rank test results obtained p value = 0.004 with a Correlation Coefficient value of -0.430, which means there is a relationship between the level of preparedness and the level of anxiety in the low category.Based on the research results, it can be concluded that there is a relationship between the level of community preparedness for earthquake and tsunami disasters and the level of community anxiety in Dusun Leko .The less the level of preparedness, the higher the level of anxiety.To be able to reduce anxiety during a disaster, efforts to increase community preparedness are needed, for example by conducting counseling about natural disasters so that a disaster-responsive society is formed.